Ongoing research into the hydrodynamic background of propulsion
On research on the hydrodynamic background of propulsion in swimming. Conclusion: I would expect that increasing swimming speed should lead to a higher pressure on the palmar side of the hand. The results suggest that you rather decrease the pressure on the dorsal side thereby increasing the pressure differential and thus generating more propulsive force. This is perfectly in line with the proposed pumped-up propulsion mechanism.